Duchowy niepokój, czyli o sumieniu słów kilka - Homa, Tomasz (Horyzonty Wychowania, 2017)
The concept of conscience is not an unambiguous term andis not infrequently exposed to the danger of reducing its characteristicdepth. This danger appears especially where it is understoodabove all, or, in extreme cases, merely as man’s abilityor his specific power involving pronouncing judgements on particulardeeds or attitudes, in terms of moral good or evil, passingover, and sometimes even forgetting about what makes it capable,as well as the space in which this distinctive process takesplace, thus constitutively belonging to the nature of this specifichuman reality.An opposed view of understanding of conscience as a judgement,the existentially experienced conscience perceived asdistinctive spiritual space marked with the sense of humannessappears – with a privileged place for meetings and growth.Meetings with oneself, with another man and with God, as well asgrowing in freedom and love, towards complete humanness.What best characterises it is the experience and understandingthat authentic self-fulfilment as a person – open with the Absolute,as well as with the whole reality – means our welfare andobligates. The emerging responsibility for oneself calls on tosearch for forms and ways, not just any, but harmonious with thediscovered sense of one’s own existence, in order to accomplishthis moral good. Whereas, the gradually emerging horizon ofsense, constitutively contributing to man’s moral awareness, notonly lightens self-understanding, but also makes us capable ofappropriate grasping of the deepest essence of good or evil ofour particular decisions. In this way, conscience becomes „thelight”, „the guide” and „the judge” of our being, our self-fulfilmentin freedom.Many a thing indicate that moral awareness and ability topronounce specific judgements, though diverse in terms of propriumtypical of each of them, indeed constitute one, dynamicand indivisible entity. Breaking it inevitably leads to limiting, andsometimes even distortion of one’s own humanness.